Abnormal characteristics of inferior vena cava and abdominal aorta among neonates with early onset septic shock - Lanlan Mi; Yiman Liu; Fei Bei; Jianhua Sun; Jun Bu; Yuqi Zhang; Weiwei Guo (Italian Journal of Pediatrics)
Abstract Background The variety of shocks in neonates, if not recognized and treated immediately, is a major cause for fatality. The use of echocardiography may improve assessment and treatment, but its reference values across gestational age (GA) and birth weight (BW) are lacking. To address the information gap, this study aimed at correlating GA and BW of newborns with nonhemodynamic abnormalities, and at evaluating the usefulness of such reference values in neonates with early onset septic (EOS) -shock. Methods A total of 200 normal newborns were enrolled as controls and subdivided into groups based on GA, BW, days of age, and patent ductus arteriosus (PDA). Echocardiography was used to document inferior vena cava diameter (IVC), inferior vena cava collapsibility index (IVC-CI), and inferior vena cava to abdominal aorta ratio (IVC/AO). In addition, 18 neonates with EOS shock were recruited and evaluated using echocardiography. Results Among the control newborns, IVC and AO were significantly increased with GA and BW (P < 0.05) but IVC-CI and IVC/AO did not correlate with GA, BW, day of age, and PDA. Compared to the control group, the EOS-shock group had significantly decreased IVC and IVC/AO, and increased IVC-CI (P < 0.05). The cut-off values for indicating EOS-shock were > 34.15% for IVC-CI, < 47.58% for IVCmin/AO, and < 66.11% for IVCmax/AO. Conclusions The IVC-CI, IVCmin/AO, and IVCmax/AO indices are applicable to all neonates. Although the number of neonates with EOS-shock in our study is small, the cut-off values showed usefulness for diagnosis. Further research is needed to determine the application of the indices in a larger population and among other populations, especially for clinical application in treatment of shock among neonates.